Development and accelerated shelf-life assessment of coconut squash: A comprehensive evaluation of physicochemical, antioxidant, and sensory attributes - Sara Shahbaz; Iahtisham-Ul-Haq; Nirmeen Nadeem; Mahnoor Siddiqui; Robert Mugabi; Aanchal Sharma; Tawfiq Alsulami; Gulzar Ahmad Nayik (Food Chemistry: X)
Value addition in food products is essential to meet changing market trends and lifestyle demands, enhancing both quality and market value. This study aimed to develop and evaluate the accelerated shelf-life of coconut squash. Five formulations with varying coconut milk concentrations (100–500 mL/L) were analyzed over 56 days at room temperature (20 °C). The Q10 method, using acid value as a spoilage factor and temperature as an acceleration factor, was employed for shelf-life prediction. Physicochemical and antioxidant properties were monitored, revealing decreases in pH, total sugars, total phytochemicals, and antioxidant activity, alongside increases in acidity, TSS, and FFA during storage. Sensory evaluation identified T5 as the optimal formulation due to its superior quality attributes and a predicted shelf life of 121 days. These findings highlight T5's potential for commercial applications as a high-quality, functional beverage.